Attitudes of Distance Learning Students Towards Employing Artificial Intelligence Technologies in Supporting Self-Learning Strategy (Journal of Hama University, 2026)
This study aimed to investigate the attitudes of distance learning students toward the use of artificial intelligence technologies in supporting the self-learning strategy, with an analysis of statistically significant differences related to some demographic variables. The study population consisted of distance learning students at Al-Zaytoonah University of Jordan in the Syrian Arab Republic. A sample of (300) male and female students was selected using stratified random sampling, including the specialties of “Classroom Teacher” and “Psychological Counseling,” with diversity in gender (male and female), academic qualification (bachelor’s and diploma), and years of experience (from one year to more than five years).The study relied on the descriptive-analytical method and used an electronic questionnaire prepared by the researcher to measure students’ attitudes toward employing artificial intelligence technologies, with validity and reliability statistically verified.The results showed that distance learning students’ attitudes toward employing artificial intelligence technologies to support self-learning were generally high. No statistically significant differences were found related to gender or academic specialty, while statistically significant differences were found favoring bachelor’s degree holders regarding academic qualification and those with more than five years of experience.The study recommended intensifying practical training programs on artificial intelligence tools within distance learning programs and integrating these technologies into curricula to enhance students’ self-learning efficiency, considering individual differences related to experience level and academic qualification.
Keywords: : Distance learning attitudes, artificial intelligence, self-learning, Al-Zaytoonah University, e-learning